Monitoring adherence to antiretroviral treatment in Brazil: an urgent challenge Monitoramento da adesão ao tratamento antirretroviral no Brasil: um urgente desafio - Gustavo Machado Rocha; Carla Jorge Machado; Francisco de Assis Acurcio; Mark Drew Crosland Guimarães (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2011)
The aim of this study was to describe the effect of non-adherence on the main laboratory outcomes, TCD4+ lymphocyte count and viral load, routinely used to monitor patients initiating treatment according to three different approaches to measure adherence to antiretroviral therapy. Among 288 participants, 22.9%, 31.9% and 74.3% were considered non-adherent, according to medical charts, self-report and pharmacy records, respectively. Depending on the adherence measures used, the average gain in TCD4+ lymphocyte count ranged from 142.4 to 195.4 cells/mm3 among adherent patients, and from 58.5 to 99.8 lymphocytes TCD4+/mm3 among those non-adherent. The average reduction on viral load ranged from 4.25 to 4.62 log copies/mL among the adherent patients, and from 1.99 to 4.07 log among those non-adherent. Monitoring antiretroviral adherence should be considered a priority in these public AIDS referral centers in order to identify patients at high risk of developing virologic failure. Early interventions are necessary in order to maintain the initial therapeutic regimens for longer periods. O objetivo deste estudo foi descrever o efeito da não-adesão nos principais desfechos laboratoriais, contagem de linfócitos TCD4+ e carga viral, rotineiramente utilizados para monitoramento de pacientes iniciando tratamento segundo três diferentes formas de medir adesão à terapia antirretroviral. Entre 288 participantes, 22,9%, 31,9% e 74,3% foram considerados não-aderentes, respectivamente, pelos registros em prontuários médicos, autorrelato e registros de dispensação nas farmácias. Dependendo da medida de adesão utilizada, o ganho médio de linfócitos TCD4+ variou de 142,4 a 195,4 células/mm³ para participantes aderentes, comparados com 58,5 a 99,8 para não-aderentes. A redução média na carga viral variou de 4,25 a 4,62 log cópias/mL entre aderentes, comparados com 1,99 a 4,07 para não-aderentes. O monitoramento da adesão à terapia antirretroviral deve ser uma prioridade nos serviços de referência de AIDS, sendo capaz de identificar pacientes com alto risco de desenvolver falência virológica e permitindo intervenções precoces com possibilidade de preservação de esquemas terapêuticos iniciais.